Soil bacterial communities in urban deciduous forests are filtered by site identity, soil chemistry, and shrub presence - Derek Griffin Wu; Vincent D’Amico; Tara Lynn Eckard Trammell (Scientific Reports)
Abstract Urban forest soils are complex environments subjected to various stressors that alter chemical and microbial properties. To understand soil chemistry and bacterial community patterns in urban forest soils with respect to site identity and multiflora rose (Rosa multiflora) invasion, soils were collected from beneath R. multiflora, native spice bush (Lindera benzoin), and uncovered ground in three forests in Newark, Delaware. High-throughput sequencing was used to analyze bacterial communities with corresponding soil chemical properties. Soil chemistry and operational taxonomic unit (OTU) communities were explained by site rather than by shrub cover type. Unlike other invasive plant studies, R. multiflora had minimal effects on either soil chemistry or bacterial communities. Phylum level bacterial communities were more uniform under shrub cover versus no cover, indicative of a generalized plant effect shaping soil microbiomes. Correlations between bacterial phyla and soil chemistry varied, with some phyla positively or negatively correlating with the same property at different sites. Filters for bacterial communities differ across forest scales, where sites and sampling location primarily correlate with OTU communities yet shrub presence mediates phylum level organization. Forest soil studies should consider location-based differences in bacterial communities and their correlations with soil chemistry before generalizing outcomes for whole macrosystems.